Staff Training and Promotion as Predictors of Teachers’ Effectiveness in Public Senior Secondary Schools in Education District II of Lagos State - Faith Omotola Oyewo (Interdisciplinary Journal Of Lifelong Learning, 2025)
This paper examined staff training and promotion as predictors of teachers’ effectiveness in public senior secondary schools in Education District II of Lagos State. A descriptive research design was used for the study. The population comprised all the 1,818 public senior secondary school teachers in Education District II, Lagos State. Two hundred teachers were selected as sample through simple random sampling technique from ten schools within Educational District II of Lagos State. Two research questions were formulated to guide the study and two hypotheses were tested. A self-developed structured type of questionnaire instrument ‘Staff Training and Promotion as Predictors of Teachers’ Effectiveness Questionnaire (STPPTEQ)’ which was thoroughly scrutinised by the two experts in the field, was used to extract information from the respondents. The instrument was confirmed valid and reliable at 0.82 coefficient. The data collected were analysed using descriptive statistical tools of frequency counts and percentage for the demographic data, mean and Standard Deviation for the research questions while inferential statistics of Pearson Product Moment Correlation (PPMC) was used to test the hypotheses. The findings showed that teachers are often denied their basic right of promotion and the Education District does not organise seminars and workshops for all cadres of personnel and principals do not give opportunities to teachers to attend in service courses. Based on the findings, the following recommendations were made; promotion should be timely and totally based on merit, teachers should be allowed to attend training programmes for extensive professional development.